Lipid changes during the canning of mackerel - Fermin M. Saavedra Cano (1981)
Mackerel (Scomber scombrus) were filleted and fillets from one side of each fish were stored at -25°C. Fillets from the other side were immersed in saturated brine for 10 minutes and canned either in simulated tomato sauce (pH 4.7) or 2% brine. Effects of the brining, heat processing and storage were studied. Iodine, Peroxide, Acid and Saponification Values in both canned and uncanned fillets were determined. The fatty acid profile was also determined for some of the samples. The analyses were carried out both on fillets with and without skin. [Continues.]